Changes in microbial community during hydrogen and methane production in two-stage thermophilic anaerobic co-digestion process from biowaste. (March 2016) - Zahedi, S.; Solera, R.; Micolucci, F.; Cavinato, C.; Bolzonella, D.
Highlights: Microbial community in a two-phase thermophilic anaerobic codigestion process was studied. Clostridium sp. constituted the major genera of Firmicutes in the first phase. Methanobacteriales constituted the major group of Archaea in the second phase. CH4 production was observed in the second phase when a ratio H2 -/acetate-utilizing methanogen of 3.6 was reached. Abstract: In this paper, the microbial community in a two-phase thermophilic anaerobic co-digestion process was investigated for its role in hydrogen and methane production, treating waste activated sludge and treating the organic fraction of municipal solid waste. In the acidogenic phase, in which hydrogen is produced, Clostridium sp. clusters represented 76% of total Firmicutes . When feeding the acidogenic effluent into the methanogenic reactors, these acidic conditions negatively influenced methanogenic microorganisms: Methanosaeta sp., ( Methanobacteriales, Methanomicrobiales, Methanococcales ) decreased by 75%, 50%, 38% and 52%, respectively. At the same time, methanogenic digestion lowered the numbers of Clostridium sp. clusters due to both pH increasing and substrate reduction, and an increase in both Firmicutes genera (non Clostridium ) and methanogenic microorganisms, especially Methanosaeta sp. (208%). This was in accordance with the observed decrease in acetic (98%) and butyric (100%) acid contents. To ensure the activity of the acetate-utilizing methanogens (AUM) and the acetogens, high ratios of H2 -utilizing methanogens (HUM)/AUM (3.6) were required.